A TLR5 mono-agonist restores inhibited immune responses to Streptococcus pneumoniae during influenza virus infection in human monocytes. - Paula T Maguire (Public Library of Science (PLoS), 2021)
Influenza A virus (IAV) predisposes individuals to often more severe secondary bacterial infections with Streptococcus pneumonia (S. pneumoniae). The outcomes of these infections may be made worse with the increase in antimicrobial resistance and a lack of new treatments to combat this. Th17 responses are crucial in clearing S. pneumoniae from the lung. We previously demonstrated that early IAV infection of human monocytes significantly reduced levels of S. pneumoniae-driven cytokines involved in the Th17 response. Here, we have further identified that IAV targets specific TLRs (TLR2, TLR4, TLR9) involved in sensing S. pneumoniae infection resulting, in a reduction in TLR agonist-induced IL-23 and TGF-β. The effect of IAV is more profound on the TLR2 and TLR9 pathways. We have established that IAV-mediated inhibition of TLR9-induction is related to a downregulation of RORC, a Th17 specific transcription factor. Other studies using mouse models demonstrated that TLR5 agonism improved the efficacy of antibiotics in the treatment of IAV/S. pneumoniae co-infections. Therefore, we investigated if TLR5 agonism could restore inhibited Th17 responses in human monocytes. Levels of pneumococcus-driven cytokines, which had previously been inhibited by IAV were not reduced in the presence of the TLR5 mono-agonist, suggesting that such treatment may overcome IAV inhibition of Th17 responses. The importance of our research is in demonstrating the IAV directly targets S. pneumoniae-associated TLR pathways. Additionally, the IAV-inhibition of Th17 responses can be restored by TLR5 agonism, which indicates that there may be a different Th17 signalling pathway which is not affected by IAV infection.